Pelvic and acetabular trauma. Issue 2 (April 2017) - Tissingh, Elizabeth K.; Taki, Hussein; Hull, Peter
Abstract: Pelvic and acetabular trauma often presents in the context of polytrauma and may cause life threatening haemodynamic instability. An understanding of anatomy, physiology and classification systems will help in the assessment of the stability of the fracture pattern and the patient. Patients should be managed according to agreed clinical guidelines within the trauma network. Early specialist input is required into decision making concerning the operative and non-operative management options.